Application of genomics and molecular genetics in date palm (Phoenix dactylifera L.) - Al-Mamari, Al-Ghaliya Humaid (2013)
Date palm (Phoenix dactylifera L.) is a diploid with 18 pairs of chromosomes and an estimated genome size of 658 Mb. It is a dioecious perennial monocot, with a long generation time (a period of 4-5 years until first flowering). Date palm is one of the major fruit crops grown in the Gulf countries and particularly in the Sultanate of Oman. Approximately 250 varieties of date palm are recorded throughout the country with evaluation and characterization based on morphological and reproductive traits (e.g. fruit color, fruit shape and fruit weight). Limited molecular characterization work has been undertaken for date palm germplasm in general and Omani date palm germplasm, in particular. The principal focus of this study was to: investigate the genetic diversity of Omani date palm germplasm and compare it with 'exotic' germplasm, to differentiate between female and male plants at the molecular level and to construct an initial genetic map for date palm.